2023
DOI: 10.1155/2023/4881952
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Magnetic Nanobiochar with Their Use in Environmental Remediation and High-Value Applications

Abstract: Magnetic nanobiochar (MNBC) is a sort of nanobiochar that has been enhanced with magnetic qualities. MNBC is made from a variety of feedstocks, including wood chips, agricultural waste, municipal sludge, animal manure, and other organic waste. These feedstocks are pyrolyzed at various temperatures to produce biochar, which is then mixed with magnetic precursors to create MNBC. Crystallinity, high porosity, specific surface area, and great catalytic activity are a few of the dynamic properties of MNBC. The majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 109 publications
(112 reference statements)
0
9
0
Order By: Relevance
“…Jin et al 55 observed that the cobalt-doped biochar of bamboo showed higher pore volume and surface area than the un-doped adsorbent, which led to greater chromium hexavalent removal capacity. Similarly, a substantial increase in pore volume and surface area was also found with an enhancement of Fe quantity on coated biochar 50 . Loading of surfactant for carbon nanotube dispersion during the preparation of carbon nanotube doped-biochar resulted in a greatly higher sorption capacity of carbon nanotube-loaded biochar for pollutants (lead and sulfapyridine) than without surfactant owing to the magnificent distribution and dispersion of carbon nanotube on the adsorbent surface 11 .…”
Section: Various Modification Techniques For the Preparation Of Funct...mentioning
confidence: 62%
See 2 more Smart Citations
“…Jin et al 55 observed that the cobalt-doped biochar of bamboo showed higher pore volume and surface area than the un-doped adsorbent, which led to greater chromium hexavalent removal capacity. Similarly, a substantial increase in pore volume and surface area was also found with an enhancement of Fe quantity on coated biochar 50 . Loading of surfactant for carbon nanotube dispersion during the preparation of carbon nanotube doped-biochar resulted in a greatly higher sorption capacity of carbon nanotube-loaded biochar for pollutants (lead and sulfapyridine) than without surfactant owing to the magnificent distribution and dispersion of carbon nanotube on the adsorbent surface 11 .…”
Section: Various Modification Techniques For the Preparation Of Funct...mentioning
confidence: 62%
“…Applying chitosan as a modifying agent, established amine functionalities on the surface of biochar to enhance its adsorption capacity and affinity to inorganic pollutants 49 . Chitosan loading on the surface of biochar can also enhance its effectiveness as a soil rectification, as well as chitosan-loaded adsorbent, may be applied as an efficient, eco-friendly, and low-cost adsorbent to decontaminate the pollutants from the environment 50 . H 2 O 2 -modified biochar derived from peanut hull surface enhanced oxygen-enrich functional groups, particularly the carboxyl group which accelerates the metals removal capacity and affinity of adsorbent 9 .…”
Section: Various Modification Techniques For the Preparation Of Funct...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although biochar research in agriculture is a well-established area, its nanosized fraction, nanobiochar, is in the early stage of scientific research. Nanobiochar is being proposed for environmental remediation, although the mechanism of action is poorly understood [53][54][55][56]. Nanobiochar has superior physicochemical properties to biochar, such as high catalytic activity, a large SSA, and high environmental mobility [53].…”
Section: Water Treatmentmentioning
confidence: 99%
“…Nanobiochar has superior physicochemical properties to biochar, such as high catalytic activity, a large SSA, and high environmental mobility [53]. The main applications of nanobiochar in environmental treatment technologies are in pollutant removal, like heavy metals, toxic organic substances, and emerging pollutants, via adsorption mechanisms like ion exchange, complexation, precipitation, electrostatic interaction, and physical adsorption [53][54][55]. As discussed above, the biochar's structure and properties depend on the raw materials and technological characteristics of the pyrolysis process, and the same is naturally observed for nanobiochar [54,55].…”
Section: Water Treatmentmentioning
confidence: 99%